(untitled) (Research, Society and Development, 2025)
Type 2 Diabetes mellitus is characterized by high blood glucose levels, which, in the long term, can progress to complications affecting important organs throughout the body. The cause of diabetes is multifactorial, but lifestyle habits such as a sedentary lifestyle and inadequate diet favor obesity and the emergence of chronic diseases such as diabetes. In addition to effective drug therapies to control the disease, new therapeutic strategies for controlling chronic hyperglycemia are being studied, such as resveratrol, a polyphenol found in plums, grapes and red fruits, and has anti-inflammatory, antioxidant and antidiabetic properties. The objective of the work was to evaluate the effects of resveratrol on the glycemic profile in type 2 diabetes mellitus. The literature review methodology was based on the selection of articles related to the topic, published in scientific databases such as PubMed and Web of Science between 2014 and 2024. Resveratrol supplementation showed promise in glycemic control in type 2 diabetics, reducing plasma glucose levels, HbA1c, in addition to improve insulin action.